Progress on multi-compartment polymeric capsules - Huang, Xin; Voit, Brigitte (Polymer Chemistry, 2013)
Recently, the construction of multi-compartment polymeric capsules has received considerable attention; for the development of next generation hollow structure carriers, multi-compartmentalization is a key requirement. In this review we give a brief overview with regard to the different preparation methods of multi-compartment polymeric capsules including self-assembly, surface-initiated polymerization, layer-by-layer assembly, emulsion-based methods, in addition to self-assembly approaches using dendrimers or hyperbranched polymers as construction units. Finally, a short summary on potential biological applications is given. © 2013 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2023-03-20